Validasi Perangkat Pembelajaran Fisika Modern dengan Model Inkuiri Terbimbing Berbantuan Media Virtual untuk Meningkatkan Kreativitas Ilmiah dan Keterampilan Proses Sains Mahasiswa - Susilawati Susilawati; Aris Doyan; Muh. Makhrus; S. Hakim (Universitas Hamzanwadi, 2020)
This research is a development research that aims to produce a modern physics learning tool with guided inquiry model assisted by virtual media. The development of this learning tool is carried out using the 4D model which consists of 4 development stages, namely the definition stage, the design stage, the develop stage, and the deseminate stage. The definition stage is carried out to identify problems, the design stage is carried out in the form of designing a guided inquiry learning device, and the dissemination stage is carried out in the form of distributing learning tools to physics education lecturers. The learning tools developed were syllabus, leasson plan, student worksheet, and tests of students' scientific creativity and science process skills. The use of learning tools with a guided inquiry model assisted by virtual media aims to help students' scientific creativity and science process skills. However, in this paper, it is focused on the validation test process through validation tests on developing the tools that are made. The final result of this research is to produce a product development of instructional models assisted inquiry model with virtual media that is valid and suitable for use.DOI: 10.29408/kpj.v4i2.2524